Kajian persilangan tiga jalur (three way cross) untuk peningkatan produksi benih padi hibrida=Evaluation of Three Way Cross for Shifting the Hybrid Rice Seed Production - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Seed production is an important component of the development and use of hybrid rice technology. The effect of three way cross on outcrossing and seed yield of Fj female parents showed high pollen sterility (> 90%) were evaluated in Research Institute for Rice, Sukamandi, 15 m asl, from October 2003 to April 2004, arranged in Randomized Complete Block Design (RCBD) with three replications. Eighteen F, derived from some crosses of indica x japonica and indica x javanica performed high pollen sterility in test cross nursery conducted in the last season (from May 2003 to September 2003), were pollinated by IR53942 (good restorer) as three way cross. Single cross of IR58025A x IR53942 was used as control. Data indicated that three combinations namely (IR68886A x Mendawak) x IR53942